Tvone’s Public Relation Strategy In The Adira Festival Event - Alya Rochyati Nafisah; Dinar Ayu Chandra Agustin (LPPM Stikosa - AWS, 2024)
As one of Indonesia's leading television networks, tvOne’s public relations (PR) possesses significant power in reaching a broad and diverse audience. In its collaborations with other companies, tvOne’s PR engages in various partnership initiatives aimed at mutual growth and success. This is evidenced by their collaboration with Adira Finance, indicating an important PR relationship. This study examines the PR strategies employed by tvOne in the context of the Adira Festival event. The objective is to understand the strategies utilized by tvOne’s PR team in planning, organizing, and executing communication strategies that support the event. This research uses a descriptive qualitative approach with data collection techniques including observation, interviews, documentation, and social media analysis. Data analysis techniques involve data reduction, data presentation, and conclusion drawing. The findings reveal that tvOne’s PR successfully leverages the P.E.N.C.I.L.S theory and effectively implements Media Partner strategies, social media strategies, publicity in mass media, collaboration with local government, support for SMEs, event activity management, tenant scheduling, SME selection, and coordination.